Effects of total saponins of Panax notoginseng on increasing PGI2 in carotid artery and decreasing TXA2 in blood platelets - SHI Lin; FAN Pan-sheng; WU Ling; FANG Ji-xi; HAN Zhi-xing (Acta Pharmacologica Sinica; Vol 11, No 1 (January 1990): Acta Pharmacologica Sinica, 2016)
Total saponins of Panax notoginseng (PNS) were given orally 100 mg/(kg.d) to rabbit for 8 wk. Aortic atherosclerotic plaque formation was restrained as compared to the control group. Radioimmunoassay was used to investigate the effects of PNS on the contents of prostacyclin in carotid artery and thromboxane A2 in blood platelets of rat. Oral administration of PNS 25,50,100 mg/(kg.d) for 10 d, the caused an increase of prostacyclin in carotid artery and a decrease of thromboxane A2 in blood platelets as compared to the control group. These results show that the anti-atherosclerotic action of PNS may be a result of the correction of the unbalance between prostacyclin and thromboxane A2.